2003
DOI: 10.1016/s1534-5807(03)00095-9
|View full text |Cite
|
Sign up to set email alerts
|

Patterning Systems—From One End of the Limb to the Other

Abstract: A combination of embryology and gene identification has led us to the current view of vertebrate limb development, in which a series of three interlocking patterning systems operate sequentially over time. This review describes current understanding of these regulatory mechanisms and how they form a framework for future analysis of limb patterning.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
164
0
1

Year Published

2008
2008
2013
2013

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 209 publications
(171 citation statements)
references
References 68 publications
3
164
0
1
Order By: Relevance
“…Rather, BMP signaling is required for initial chondrogenesis as outlined above and BMP/pSmad signaling appears to be the driving force for the outgrowth of the digit condensations by means of distally directed chondrogenesis. Montero et al (2008) furthermore showed that the integrity of the DC/ PFR required AER signaling, which links the DC/PFR to the elongation model proposed by Sanz-Ezquerro and Tickle (2003). These studies altogether suggest that the outgrowth of digit condensations depends on a timely and spatially defined input of strong BMP/Smad1/5/8 signaling.…”
Section: Developmental Dynamicsmentioning
confidence: 59%
See 4 more Smart Citations
“…Rather, BMP signaling is required for initial chondrogenesis as outlined above and BMP/pSmad signaling appears to be the driving force for the outgrowth of the digit condensations by means of distally directed chondrogenesis. Montero et al (2008) furthermore showed that the integrity of the DC/ PFR required AER signaling, which links the DC/PFR to the elongation model proposed by Sanz-Ezquerro and Tickle (2003). These studies altogether suggest that the outgrowth of digit condensations depends on a timely and spatially defined input of strong BMP/Smad1/5/8 signaling.…”
Section: Developmental Dynamicsmentioning
confidence: 59%
“…Outgrowth of the limb bud is under the control of fibroblast growth factor (Fgf) signaling from the apical ectodermal ridge (AER), a thickened ectodermal structure that runs along the dorsoventral border of the limb bud (Niswander et al, 1993;Sun et al, 2002). Besides the AER, other signaling centers such as the zone of polarizing activity (ZPA) in the posterior mesenchyme and the dorsal ectoderm specify the three spatial axes of the limb bud (reviewed in Tickle, 2003Tickle, , 2006. These patterning mechanisms in the end generate a morphogenetic field that conveys the information for patterning the skeletal elements as well as other structures in the limb (see e.g., Zeller et al, 2009).…”
Section: Overviewmentioning
confidence: 99%
See 3 more Smart Citations